Introduction - Cleary, Shannon E. (Columbia Journal of Gender and Law, 2015)
June 26, 2013 was an impossibly long day. At the time, I was living and interning in Kathmandu, Nepal, which is ten hours and forty-five minutes ahead of Washington, D.C. and the Supreme Court. I awoke to reports of Wendy Davis’s ongoing filibuster in Texas and ran two miles, through monsoon puddles, wearing my own pink sneakers, all the way to my office, where I could use the more reliable intemet to stream coverage. I did not even attempt to explain the procedures of a filibuster to my officemate, saying simply that there was a woman in the United States breaking barriers for reproductive rights.